Design of Air Pressure Measuring Devices Using a Barometric Pressure 280 (BMP280) Sensor Based on Arduino Uno - Khaery, Miftahul; Pratama, Abel Harditio; Wipradnyana, Pande; Gunawan, Anak Agung Ngurah (BULETIN FISIKA, 2020)
An air pressure gauge instrument has been successfully made using the Arduino Uno-based BMP280 sensor. This instrument was standardized by using a standard measuring instrument at the Central Bureau of Meteorology, Climatology and Geophysics (BMKG) Region III Tuban Bali.  It was obtained that the calibration equation is y = 1.0022x - 1.8907 with a coefficient of determination (R 2 ) of 0.99998. This shows that the instrument made has a high degree of accuracy and precision.